Experience of skin disease and relationships with healthcare providers: a qualitative study of Traveller women in Ireland. (12th April 2019) - Gilhooley, E.; Daly, S.; Gallagher, O.; Glacken, M.; McKenna, D.
Summary: Background: Significant health disparities exist between members of the Travelling community and those of the general population. Barriers to Traveller engagement with health services include the experience or perception of discrimination, and cultural and health literacy barriers. Experience of skin disease and interactions with healthcare providers has not been widely explored in this ethnic minority. The formation of positive relationships between the Travelling community and healthcare providers is important in the promotion of treatment adherence and improving health outcomes. Objectives: To investigate Travellers' experience of skin disease and their relationships with healthcare providers. Methods: Focus groups were conducted with a purposive sample of female members of the Irish Travelling community with experience of skin health issues, between January 2018 and April 2018. Three focus groups were conducted at three separate locations with 10 participants in each group. Themes were identified from the focus group transcripts using an inductive thematic analysis framework. Results: Emergent themes surrounding relationships between Travellers and healthcare providers included health literacy, discrimination, information inconsistency, trust and communication. Factors that were valued in the creation of positive relationships included an appreciation of varying degrees of health literacy, the provision of sufficient information tailored to an individual's needs and a demonstration of cultural competence. Conclusions: Dermatologists are well placed to provide practical, customized, treatment guidance and engage patients while integrating their culturally based beliefs. Abstract : What's already known about this topic? Significant health disparities exist between Travellers and the general population. A number of social, cultural and economic factors create challenges in the effective engagement of Travellers with healthcare services and providers. The experience of skin disease and relationships with healthcare providers has not been widely explored in Travellers. What does this study add? This qualitative study employed focus groups in the exploration of factors that determine the quality of interactions between members of the Travelling community and their healthcare providers. Demonstration of health literacy and cultural competence by health providers has a positive impact on the quality of relationships between Travellers and health providers. What are the clinical implications of this work? Potential opportunities to enhance the quality of relationships between health providers and under‐represented minorities are explored. Linked Editorial:  Nelson et al. Br J Dermatol 2019; 180 :1271–1273 . Linked Comment:  Newton and Smith. Br J Dermatol 2019; 180 :1290–1291 . Plain language summary available online Respond to this article